Zastosowanie preparatu bevacizumab w leczeniu uzupełniającym jaskry zamkniętego kąta – opis przypadku - Helemejko, Iwona; Jurowska-Liput, Joanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
We report the use of bevacizumab (Avastin) as an additional strategy in angle closure glaucoma based on the case of 47 years old male qualified to cataract removal as anti-glaucoma procedure, in whom we observed iris and lens neovascularization. As a first step we administered 1.25 mg of bevacizumab into the anterior chamber. Iris as well as lens neovasularization completely disappeared after 48 hours later. Finally after lens removal we achieved deeper anterior chamber, reduction and stabilization of intraocular pressure without necessity of administration hipotensive agents, and improvement of visual acuity.